Everybody belongs : changing negative attitudes toward classmates with disabilities - Shapiro, Arthur H., 1938- (Garland reference library of social science, 1999)
The evil prosthesis of Captain Hook, the comical speech of Porky Pig, and the bumbling antics of Mr. Magoo are all examples of images in our culture which can become the basis of negative attitudes and subliminal prejudice towards persons with disabilities. These attitudes influence and underlie discriminatory acts, resulting in negative treatment and segregation. A teacher's ability to recognize and counter such images may well determine the success of inclusion and mainstreaming programs in our schools and society. Well-researched and well-written, this book offers practical guidance as grou.